El Excentrico, 1961-10-05 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
October 5, 1961 [5 de octubre de 1961]. Ano 11, No 24. Cover has a photo of columnist Esther Medina on left and Angel Gonzalez on the right with headline "Our celebrated columnist Esther Medina weds."